2013
DOI: 10.4103/1119-3077.106747
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychological illness on outcome of corrosive esophageal injury

Abstract: Early recognition of psychosocial distress is important to prevent deliberate self-harm. Counter-intuitively, a previous history of psychopathology limits esophageal injury by early presentation and therefore improve chances of a good surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
(16 reference statements)
0
9
0
1
Order By: Relevance
“…The occurrence of corrosive ingestion in children is mostly accidental, but the majority of adult cases (70.5%) are intentional self-harm [ 2 , 6 ]. Psychiatric disorders and socioeconomic stresses are considered the most common reasons for corrosive ingestion [ 7 ]. Legislative efforts to identify individuals with psychosocial distress for appropriate therapy are important for reducing the incidence of deliberate ingestion of corrosive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of corrosive ingestion in children is mostly accidental, but the majority of adult cases (70.5%) are intentional self-harm [ 2 , 6 ]. Psychiatric disorders and socioeconomic stresses are considered the most common reasons for corrosive ingestion [ 7 ]. Legislative efforts to identify individuals with psychosocial distress for appropriate therapy are important for reducing the incidence of deliberate ingestion of corrosive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Ogunrombi et al 16 have reported 27 patients with psychopathologic history, who had a limited degree of caustic injuries and better surgical outcomes. In contrast, our experiences demonstrated that PCs were predictors of severe GI tract injuries and involved greater consumption of healthcare resources, more early complications/delayed sequelae, less preservation of the native esophagus/stomach, and poorer long-term survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]5,6,[10][11][12][13][14] Patient age, sex, comorbidities, complications, treatment choices, and socioeconomic status have important roles in survival outcomes and postinjury quality of life. 1,2,4,6,7,12,13,[15][16][17][18][19][20][21] Preventive measures have been widely advocated. 1,6,10,[22][23][24][25] However, the effectiveness of precautions appears unsatisfactory in adults, among whom suicidal intents and deliberate self-harm accounts for the majority of cases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations